A field guide to lies : critical thinking with statistics and the scientific method - Levitin, Daniel J., 1957- (Dutton, 2016)
We are bombarded with more information each day than our brains can process—especially in election season. It’s raining bad data, half-truths, and even outright lies. Daniel J. Levitin shows how to recognize misleading announcements, statistics, graphs, and written reports, revealing the ways lying weasels can use them. Levitin groups his field guide into two categories—statistical information and faulty arguments—ultimately showing how science is the bedrock of critical thinking. Readers learn to avoid the extremes of passive gullibility and cynical rejection. His accessible guide helps anyone wake up to a whole lot of things that aren’t so—and catch some weasels in their tracks!